Men of Valor : Buried Secrets : Book 1 - Hannon, Irene (Grand Rapids, Michigan : Revell, a division of Baker Publishing Group, 2015)
"After seven years as a Chicago homicide detective, Lisa Grant has hit a wall. Ready for a kinder, gentler life, she takes a job as a small-town police chief. But the discovery of a human skeleton by a construction crew at the edge of town taxes the resources of her department. A call for assistance brings detective Mac McGregor, an ex-Navy SEAL, to her doorstep. As they work to solve the mystery behind the unmarked grave, danger begins to shadow them. Someone doesn't want this dead person telling any tales--and will stop at nothing to make certain a life-shattering secret stays buried"--Amazon.com.
Keywords: Women police chiefs -- Fiction; Murder -- Fiction -- Investigation; Mystery fiction; Christian fiction